Analisis Teori Hukum terhadap Penegakan Tindak Pidana Pemalsuan Uang: Analisis Teori Hukum Positif dan Teori Hukum Responsif - Panca Gunawan Harefa; Idham Idham; Erniyanti Erniyanti (Penerbit Goodwood, 2023)
Purpose: The purpose of writing this journal is to find out the legal arrangements for the crime of counterfeiting money, and to know the analysis of the implementation of law enforcement against the crime of counterfeiting money. Method: The method used is a normative approach, namely through library research, and an empirical approach, namely through field research by conducting a series of interviews with respondents and informants to obtain field data. Result: The results of the study show that legal arrangements for the crime of counterfeiting money are regulated in the Currency Act and in the Criminal Code which explains that everyone, both individually and as a group, who counterfeits rupiah currency will be punished with imprisonment for a maximum of 10 (ten) years and a maximum fine of Rp. 10,000,000,000.00 (ten billion rupiah). In addition, based on the provisions of Article 244 of the Criminal Code, it is explained that anyone, either individually or as a group, who makes counterfeit money with the intention of circulating it will be subject to imprisonment for a maximum of fifteen years. Analysis of the implementation of law enforcement against the crime of counterfeiting money is still not optimal, especially with regard to the imposition of criminal sanctions which are still very low, so that the crime of counterfeiting currency is considered not a serious crime. This is possible because the proof is relatively easy. There has been a paradigm shift regarding currency, not just a means of payment, but money can be used as a tool for politics, economic colonization and so on.